#BeatThePot: Strategies and Discourses of Women’s Protests in Zimbabwe - Chipuriro, Rejoice (Atlantis, 2023)
This paper focuses on strategies deployed by women and discourses of women’s collective action in the #BeatThePot strike which took place alongside popular protests against Mugabe and the failures of ZANU-PF led government in Zimbabwe. Using Judith Butler’s ideas on “bodies in alliance and the politics of the street,” I theorize how women as gendered “bodies congregate, move, speak and strike together as they claim public space into political spaces” (2015, 70). I interrogate women’s use of embodiment as a strategy involving the metaphor of both the “labouring mothering body” and as “bodies that strike,” which demonstrates how women in Zimbabwe confronted violent political, economic, and socio-cultural limits imposed on their bodies. In this strike, women challenged the silencing of women’s public political work and refused to be relegated to the invisible margins of domesticized and undervalued reproductive labour. Thus, through the #BeatThePot protest, I demonstrate how women in Zimbabwe have engaged in body work to a confront violent regime and how they have borne on their bodies violent reprisal through sexual attacks, abductions, incarcerations, torture, and even loss of life. The paper concludes that the feminized body is a site of violent struggle for autonomy and that through collective action women in Zimbabwe have sought to confront and transform the repressive state.